Epidemiological Characteristics And Trends Of Suicidal Deaths In Autopsied Cases: A Retrospective Study From A Tertiary Centre - K K, Ashique; S Jirli, Prasanna; S, Shanu (Journal of Forensic Medicine and Toxicology, 2026)
Background: Suicide is a major public health challenge worldwide, with India contributing substantially to  the global burden. Between 1990 and 2010, suicides increased globally by 32%, and in 2022 India reported over  170,000 cases, marking a 4.2% rise from the previous year. This study aimed to analyze the socio-demograph ic profile of suicidal deaths autopsied at a tertiary care centre, assess the distribution and methods of suicide  with particular emphasis on hanging and poisoning, and identify contributory factors influencing these deaths. Methods: A retrospective descriptive study was conducted in the Department of Forensic Medicine, Jawaharlal  Nehru Medical College, Belagavi, from January 2023 to December 2024. Out of 348 medico-legal autopsies, 61  confirmed suicide cases with complete records were included. Data were collected from post-mortem reports, police  inquest papers, and hospital records. Demographic variables and methods of suicide were documented. Analysis was  performed using SPSS v24.0, with Chi-square test applied to assess associations (p < 0.05 consideredSignificant). Results: Of 61 suicide cases, 72.1% were males and 32.8% females. The highest proportion was aged 25–34  years (31.1%) followed by 15–24 years. Most victims were from below poverty line families (72.1%) and had  only primary or middle school education. Poisoning was the most common method (83.6%), followed by hanging  (16.4%). Statistically significant associations were not observed with age, sex, and education and economic status. Conclusion: Young adult males from socioeconomically disadvantaged backgrounds were most affected. Poi soning predominated, highlighting the need for targeted mental health interventions, awareness programs, and  stricter pesticide regulation.
Keywords: Epidemiology; Suicide; Hanging; Poisoning